ANALISIS KELEBIHAN DAN KEKURANGAN SCHOOLOGY DENGAN GOOGLE SITE UNTUK MEMAKSIMALKAN PEMBELAJARAN DARING DIMASA COVID 19 (Universitas PGRI Sumatera Barat, 2022)
AbstractEvery platform in use will always evolve with the times. As it is felt at the moment, when there was a covid-19 Pandemic in this country, one of the differences that were felt was in the field of Education. The implementation of learning which is generally faced to face must be replaced with Online Learning. Therefore it must be able to utilize existing technology to maximize Online Learning. This study aims to: (1) analyze the strengths and weaknesses of Schoology and Google Site; (2) knowing how to maximize online learning in the covid-19 era. This research is qualitative research using qualitative descriptive methods. The results of this study are (1) product in the form of analyzing the advantages and disadvantages of Schoology and google site by experts. Thus, it can be concluded that each platform will have its own strengths and weaknesses, one of the strengths is that it can be used anywhere and anytime, while one of the disadvantages is constrained by the signal. as a user can maximize it by providing understanding and education to platform users to optimize online learning, as one of the media of Learning Implementation during the covid-19 period. And new and interesting learning facilities are needed for users to avoid boredom and make it easier to master the learning material.